Indoor Color and Space Humanized Design Based on Emotional Needs - Xu, Yunkai; Wu, Shan (Frontiers in Psychology, 2022)
The increase in emotional consumption reflects the increased emotional appeal of people in modern life. As a place for people's daily life and consumption, the indoor environment has been regarded as a symbol of quality of life and aesthetic taste. The purpose of this paper is to study how to analyze and study the color factor and space humanization in interior design based on emotional needs, and describe the neural network. This paper puts forward the problem of emotional needs, which is based on the neural network model, and then elaborates on its concept and related algorithms, and designs and analyzes the case design and analysis of the humanized design of interior color and space based on emotional needs. The experimental results show that in the evaluation of the emotional needs of indoor environment users, the emotional needs of users for the three levels are all above 3.00. Users have the highest emotional needs at the usage level, reaching 4.24. It shows that users pay more attention to the practical value of the indoor environment, and hope to obtain a pleasant emotional experience by meeting the needs of practical value.